A Comparative Study on Chemical Composition, Antileishmanial and Cytotoxic Activities of the Essential Oils from Leaves of Guarea macrophylla (Meliaceae) from Two Different Regions of Sao Paulo State, Brazil, Using Multivariate Statistical Analysis - Oliveira, Emerson A.; Martins, Euder G. A.; Soares, Marisi G.; Chagas-Paula, Daniela A.; Passero, Luiz F. D. [UNESP]; Sartorelli, Patricia; Baldim, Joao L.; Lago, Joao Henrique G. (Soc Brasileira Quimica, 2019)
Meliaceae representatives are economically important in several aspects including the production of highly prized woods (mahogany, cedar, etc.), constituents for cosmetics, and insecticides. The present study aimed to verify the chemical composition as well as leishmanicidal and cytotoxic potential of essential oils from leaves of two different populations of Guarea macrophylla collected at cities of Sao Paulo (population I) and Cubatao (population II), Sao Paulo State, Brazil. Chemically, the oils showed the predominance of sesquiterpenes: cis-beta-guaiene, bicyclogermacrene, viridiflorol, and isolongifolan-7 alpha-ol from population I and alpha-copaene, E-caryophyllene, cis-beta-guaiene, and gamma-amorphene from population II. In vitro antileishmanial activity against promastigote forms of Leishmania (L.) amazonensis of essential oils was evaluated and displayed 50% effective concentration (EC50) values ranging from 11.8 to 20.5 mu g mL(-1). Furthermore, toxicity against peritoneal macrophages of BALB/c mice was observed, with 50% cytotoxic concentration (CC50) ranging from 17.7 to > 100 mu g mL(-1). Multivariate statistical analysis revealed the influence of each constituent of the oils against L. amazonensis being 1,10-di-epi-cubenol, alpha-amorphene, E-caryophyllene, isopimara-7,15-diene, and beta-elemene associated with the antileishmanial potential.
Keywords: Guarea macrophylla; 1,10-di-epi-cubenol; multivariate statistical analysis; antileishmanial activity